A Land of Five Languages: Material Culture, Communities and Identity in Northumbria, 600-867 CE - Webb, Sian (2021)
This thesis examines the identities that developed, coalesced and evolved over time in the Kingdom of Northumbria circa 600 CE and 867 CE and the methods and materials through which they were expressed in different regions using an interdisciplinary lens synthesising material culture and written evidence. Northumbria at it largest covered a considerable area of land and varying terrain in northern Britain. Considering this, one of the key questions pursued through this thesis is whether a shared Kingdom-wide sense of Northumbrian identity existed in the kingdom. If a shared identity did exist, how far through the social hierarchy did this identity permeate? Was this a specialised identity shared among elite spheres of society, or was it open to a larger proportion of the Northumbrian population? Finally, how did this kingdom-wide identity interact with localised and regional identities felt in different areas of Northumbria? The main aim through this work is that this exploration moves beyond elite groups in secular and ecclesiastic life and incorporate the wider hierarchy. In order to do so, an interdisciplinary approach has been taken using the presence, utilisation and iconography of archaeology and material culture throughout the kingdom and the social and cultural networks that emerge through these artefacts. This discussion is aided by the use of textual vignettes to open an inroad into the material remains and highlight the lived experience of the individuals who made and used these objects.